Experiences of cardiac care nurses related to the management and delayed removal of trans-radial band of patients at a private tertiary care hospital, Islamabad - Ahad, Shakeel; Idrees, Sobia; Dhamani, Khairunnisa Aziz; Khan, Sadia Farhan (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the experiences of cardiac care nurses in managing transradial band of patients in a tertiary care setting. Method: The exploratory, descriptive, qualitative study was conducted at a private-sector tertiary care hospital in Islamabad, Pakistan, from March to September 2021, and comprised registered cardiac care nurses with >6 months of relevant experience. Data was collected through face-to-face interviews using a semi-structured interview guide. Data was analysed qualitatively using the Creswell and Creswell framework. Results: Of the 10 nurses, 5(50%) were males and 5(50%) were females. In terms of age, 5(50%) were aged <25 years. Cardiac specialisation had been done by 2(20%) nurses, and none of the subjects had formal training related to transradial band. The main theme that emerged from the data was nurses’ management of patients with transradial band, and the three categories were nurses’ knowledge and practices about transradial band, reasons for delayed transradial band removal, and strategies to minimise complications. Conclusion: To minimise transradial band-related complications, in-service training of nurses and ensuring a safe nurse-patient ratio are necessary. Key Words: Assessment, Complications, Cardiac care nurses, Radial angiography, Transradial band.